KEPEMILIKAN MANAJERIAL DAN INTENSITAS PERSEDIAAN DALAM MENGHEMAT PAJAK PADA SEKTOR INDUSTRI DASAR DAN KIMIA TAHUN 2020-2022 - Sibuea, Shane Joyson; Rinendy, Jhon (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2023)
This research aims to investigate the extent to which companies can reduce their tax burden through the relationship between managerial ownership and inventory intensity concerning tax-saving practices without violating applicable laws. The study employs a quantitative method with a population of 71 companies, and 27 companies meeting the criteria were selected as samples using purposive sampling. The research focused on companies in the basic and chemical industries during the period 2020-2022. The findings indicate that managerial ownership, which refers to the ownership of the company by those who manage it, does not significantly impact the company's tax avoidance practices. Similarly, the amount of inventory stored in the company's warehouse does not have a significant effect. Therefore, it can be concluded that how the company owners manage the business and the quantity of inventory in the company's warehouse do not have a substantial influence on the company's tax avoidance strategies.